2022
DOI: 10.1097/yct.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Prophylactic Management of Postictal Agitation in Electroconvulsive Therapy

Abstract: Postictal agitation (PIA) is a common adverse effect of electroconvulsive therapy (ECT), a treatment used for a variety of psychiatric disorders. Because of risk of harm to patients and health providers when patients develop PIA, its acute management and prophylaxis are of vital importance for ECT practitioners. This article describes PIA risk factors, as well as practical steps to manage this ECT complication. Nonpharmacologic patient safety interventions are critical components of PIA management. Benzodiazep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…The use of dexmedetomidine to prevent PIA after ECT was the most recently described in two reviews that summarized the evidence thus far ( 12 , 36 ). In contrast to our results, Li et al ( 12 ) performed a meta-analysis on two studies ( 17 , 26 ) to investigate the effect of dexmedetomidine on PIA and found no statistically significant preventative effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of dexmedetomidine to prevent PIA after ECT was the most recently described in two reviews that summarized the evidence thus far ( 12 , 36 ). In contrast to our results, Li et al ( 12 ) performed a meta-analysis on two studies ( 17 , 26 ) to investigate the effect of dexmedetomidine on PIA and found no statistically significant preventative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of dexmedetomidine (to reduce the mean EAS score as opposed to placebo) in this meta-analysis was mostly measured on “relaxed and awake” patients. In addition, Sterina et al ( 36 ) recently published a narrative review on the acute and prophylactic interventions for PIA after ECT. They described various (non-) pharmacological interventions that could be attempted to prevent or treat PIA, including dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation